Spatio-temporal dynamics of milk production in Brazil - Bacchi, Matheus Demambre; Almeida, Alexandre Nunes; Telles, Tiago Santos (Semina: Ciências Agrárias, 2022)
The milk production chain has relevance for the Brazilian economy, generating jobs and income. In addition, milk production, because of family-based farms, has an important social function. However, milk production is spatially heterogeneous in Brazil, especially due to the different technological patterns of production. In this context, the objective of this study was to verify the spatio-temporal distribution and dynamics of milk production in Brazil. For this purpose, milk production in Brazil in 2000 and 2016 was analyzed. The Brazilian microregions that specialize in milk production were identified using location quotient (LQ). An exploratory analysis of spatial data and Moran's I were used to measure spatial autocorrelation among regions. Finally, principal component analysis (PCA) was used to assess the grouping relationships of variables as a function of the regions that specialize in milk production. Between 2000 and 2016, there was a decrease in the number of microregions that specialize in milk production. Thus, in 2016, approximately 20% of the microregions and over 22% of Brazilian municipalities specialized in milk production. The microregions and municipalities that specialize in milk production were concentrated mainly in the states of Minas Gerais and Goiás and in the Southern region of Brazil. There was an increase in milk productivity in all regions of the country, especially in those regions where production was concentrated. The formation of high-high clusters was found in the most productive regions of the country, i.e., in the South and Southeast, where the effects of technological spillover were observed, and the formation of low-low clusters was observed in the less productive regions, i.e., in the North and Northeast. Two main components were formed. The first component aggregated variables related to milk production in volume, and the second component aggregated variables inherent to productivity. It was possible to verify the recent growth in milk production and productivity in the country as well as to demonstrate the heterogeneity in production. Although there was a decrease in the number of microregions and municipalities that specialize in milk production, there was a concentration and increase in milk production and productivity in Brazil.